2016
DOI: 10.1039/c6cs00083e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and semisynthetic approaches to study and target deubiquitinases

Abstract: Ubiquitination is a key posttranslational modification, which affects numerous biological processes and is reversed by a class of enzymes known as deubiquitinases (DUBs). This family of enzymes cleaves mono-ubiquitin or poly-ubiquitin chains from a target protein through different mechanisms and mode of interactions with their substrates. Studying the role of DUBs in health and diseases has been a major goal for many laboratories both in academia and in industry. However, the field has been challenged by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 200 publications
(308 reference statements)
0
63
0
1
Order By: Relevance
“…[47] Therefore, failure in its regulation can lead to several pathologies,f or example,cancer and neurodegenerative disease.While aprotein modified with the specific Ub chain can proceed to degradation, this process is further complicated by the activity of DUBs,which remove Ub units from proteins to affect Ub signaling.T he largest sub family of Cys protease DUBs-Ub specific proteases (USPs) [26,47] is involved in av ariety of regulatory processes and has been implicated in various diseases.D espite progress in studying the function of many USPs,c omprehensive understanding of their structure,s pecificities,a nd cellular function is still lacking for many of its members. [47] Therefore, failure in its regulation can lead to several pathologies,f or example,cancer and neurodegenerative disease.While aprotein modified with the specific Ub chain can proceed to degradation, this process is further complicated by the activity of DUBs,which remove Ub units from proteins to affect Ub signaling.T he largest sub family of Cys protease DUBs-Ub specific proteases (USPs) [26,47] is involved in av ariety of regulatory processes and has been implicated in various diseases.D espite progress in studying the function of many USPs,c omprehensive understanding of their structure,s pecificities,a nd cellular function is still lacking for many of its members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] Therefore, failure in its regulation can lead to several pathologies,f or example,cancer and neurodegenerative disease.While aprotein modified with the specific Ub chain can proceed to degradation, this process is further complicated by the activity of DUBs,which remove Ub units from proteins to affect Ub signaling.T he largest sub family of Cys protease DUBs-Ub specific proteases (USPs) [26,47] is involved in av ariety of regulatory processes and has been implicated in various diseases.D espite progress in studying the function of many USPs,c omprehensive understanding of their structure,s pecificities,a nd cellular function is still lacking for many of its members. [47] Therefore, failure in its regulation can lead to several pathologies,f or example,cancer and neurodegenerative disease.While aprotein modified with the specific Ub chain can proceed to degradation, this process is further complicated by the activity of DUBs,which remove Ub units from proteins to affect Ub signaling.T he largest sub family of Cys protease DUBs-Ub specific proteases (USPs) [26,47] is involved in av ariety of regulatory processes and has been implicated in various diseases.D espite progress in studying the function of many USPs,c omprehensive understanding of their structure,s pecificities,a nd cellular function is still lacking for many of its members.…”
Section: Resultsmentioning
confidence: 99%
“…[26] Notably,the high similarity of the active sites between many USPs hinders the development of selective inhibitors.T odate [26] Notably,the high similarity of the active sites between many USPs hinders the development of selective inhibitors.T odate …”
Section: Resultsmentioning
confidence: 99%
“…8,9 Recent studies revealed that DUBs are susceptible to hydrogen peroxide, suggesting a potential way of regulating their cellular activity under oxidative stress (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…13 DUBs are hence emerging as promising drug targets, and their targeting via a novel mechanism of inhibition has become a major goal in academia and in industry. 9 …”
Section: Introductionmentioning
confidence: 99%
“…[12] In these examples,anelectrophile was placed between the two Ub units to trap the catalytic Cys residue of the specific DUB,w hereby the linkage type dictates the specificity of the DUB.For example, our group temporally incorporated aC ys residue into as pecific Lyss ide chain in Ub to enable ligation with synthetic Ub(1-75)-thioester,f ollowed by dehydroalanine (DHA) formation to serve as atrap for the DBU catalytic Cys residue. [13] However,d espite aw ide range of applicability of these tools,n ot every protein target is synthetically or even semisynthetically accessible,a nd ag eneral strategy for the preparation of ubiquitinated protein ABPs is highly desirable. Themain obstacle in designing such ap robe,h owever, is the nature of the ubiquitinated protein substrate.Chemical protein synthesis is am ajor tool for the preparation of both ubiquitinated proteins and diUb probes with ad efined linkage type.…”
mentioning
confidence: 99%